2021
DOI: 10.3390/en14248204
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Environmental Benefits for Electricity Grids from Spatiotemporal Optimization of Electric Vehicle Charging

Abstract: This article addresses the problem of estimating the potential economic and environmental gains for utility grids of shifting the electric-vehicle (EV) charging time and location. The current literature on shifting EV charging loads has been limited by real-world data availability and has typically therefore relied on simulated studies. Collaborating with a large automobile company and a major utility grid operator in California, this research used actual EV operational data and grid-operation data including l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Instead, we use conversion factors for well-to-tank and tank-to-wheel emissions. It is found that with an optimal operation, the electric feet operation can greatly improve the economic and environmental performance of electricity generation [43]. Te current work can improve by incorporating the sources and methods of electricity generation for the overall economic, environmental, and social costs.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…Instead, we use conversion factors for well-to-tank and tank-to-wheel emissions. It is found that with an optimal operation, the electric feet operation can greatly improve the economic and environmental performance of electricity generation [43]. Te current work can improve by incorporating the sources and methods of electricity generation for the overall economic, environmental, and social costs.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…The notion of symmetric is proposed in this work by using several approaches to identify the best condition of a power grid, including the cuckoo search algorithm (CSA), genetic algorithm (GA), and simulated annealing algorithm (SAA) [52]. Throughout this analysis, the best feasible earnings for electrical-grid suppliers were determined by changing the time and location of charging a statistical sample of EVs [53]. A thorough HEV modeling proposed approach is based on a rule-based control approach described in this work.…”
Section: Evs Planningmentioning
confidence: 99%